Eternal Sunshine of the Spotless Mind, Memory Erasure, and the Problem of Personal Identity - Giorgina Samira Paiella (Journal of Science Fiction and Philosophy, 2020)
Michel Gondry and Charlie Kaufman’s 2004 Eternal Sunshine of the Spotless Mind, which celebrated its fifteenth anniversary in 2019, is an extended thought experiment on the nature of memory, minds, and persons. The memory erasure thought experiment presented in the film—and its implications for personal identity—raises poignant questions for the ethicist, epistemologist, neuroscientist, metaphysician, and cognitive scientist. In this paper, I explore the rich insights the film has to offer interdisciplinary studies of memory, providing a case study in how narrative can uniquely contribute to memory research, while also maintaining philosophical rigor and fidelity to scientific discoveries about memory. Turning to the philosophical implications of memory erasure, I consider memory erasure in the context of several leading views of personal identity and proposed answers to the persistence question of personal identity, assessing the challenges and complications that the memory erasure thought experiment brought to life by Eternal Sunshine poses to these theories. I argue that the psychological continuity view of personal identity—in its various iterations—does not allow an individual to truly survive the memory erasure procedure. The memory erasure thought experiment presented in Eternal Sunshine—and its metaphysical and epistemological consequences—reveal how we establish the relationship between memories and selfhood, how to define personhood in the presence of both hypothetical and real-world memory loss, and what experiences we value in human life.